Acrylamide induces spatiotemporal metabolic profiling disturbance via targeting taurine and hypotaurine metabolism during early zebrafish development - Anli Wang; Jia Zeng; Xiaoran Song; Yingyu Huang; Jianxin Yao; Li Zhu; Yuchen Gao; Binjie Wang; Yuanzhao Wu; Zhongshi Xu; Ruonan Zheng; Yazhou Qin; et al. (Food Frontiers)
Abstract Acrylamide, an endocrine‐disrupting emerging contaminant from both the environment and food processing, has been linked to cardiac developmental toxicity in zebrafish. However, the mechanisms involved in the cardiac developmental toxicity from long‐term exposure to acrylamide remain unclear. This study provides in‐depth evidence on the metabolic regulation of zebrafish embryos with acrylamide exposure. A comprehensive metabolites analysis of four different acrylamide exposures (0, 0.5, 1.0, and 2.0 mM) at different zebrafish developmental stages (6, 24, 48, 72, 96, and 120 h post fertilization, hpf) was performed. Metabolite changes throughout the zebrafish development (6–120 hpf) were closely associated with taurine and hypotaurine metabolism. The pattern of significantly changed metabolites revealed that acrylamide strongly disrupts taurine and hypotaurine metabolism related to a deficient cardiovascular system. Moreover, acrylamide exposure disrupted the de novo synthesis of taurine via cysteine sulfinic acid decarboxylase during early zebrafish embryogenesis. In addition, taurine supplementation (10 mM) effectively alleviates acrylamide‐induced deficient cardiovascular system. Our results demonstrate that acrylamide exposure has a detrimental effect on early heart development in zebrafish due to the inhibition of de novo synthesis of taurine.